Displacing the Anthropocene: Colonisation, extinction and the unruliness of nature in Palestine. (March 2022) - Salih, Ruba; Corry, Olaf
Recent 'Anthropocene' commentaries have argued that as humans have become decisively entangled in natural systems, they collectively became a geological species-agent potentially becoming aware of its own place in the deep history of planetary time. Through this, the argument goes, a pre-political collective consciousness could emerge, paving the way for a progressive construction of a common world, beyond particularistic justice-claims. The reverse case is made in scholarship of settler colonialism: the Anthropocene is rooted in histories of settler colonial violence and is deeply tied up with the dispossession and 'extinction' of Indigenous life-worlds. In this article, we foreground nature–human entanglement as crucial for understanding the operations but also the instability of settler colonialism in Palestine. We suggest that fractures and openings become legible when paying attention to the 'afterlife' of nature that was erased due to its enmeshment with Indigenous people. We provide a historical and ethnographic account of past and emerging entanglements between Palestinians refugees and their nature, ultimately arguing that indigeneity is recalcitrant to obliteration. With that in mind, we return to the Anthropocene's focus on universal human extinction and ethical consciousness by critically engaging with it from the standpoint of colonised and displaced Indigenous populations, like the Palestinian refugees. We conclude by arguing that only when the profoundly unequal access to Life entrenched in settler colonialism is foregrounded and addressed, does a real possibility of recognising any common, global vulnerability that the species faces emerge.